A prospective study on meconium-stained liquor and neonatal outcome in correlation with cardiotocography in a teritiary care centre - Divya, Somavarapu; Rangappa, Sheela Shikarepura (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: The presence of meconium-stained liquor is assumed to be definitive cause of foetal distress, due to hypoxia. The aim of the study was to analyse the risk factors, route of delivery and neonatal outcome in correlation with foetal CTG. Methods: It was a prospective study of 100 women with term pregnancy in labour room with meconium-stained liquor in Department of Obstetrics at Sri Devaraj Medical College, Kolar. The period was from 01st August 2023 to 31st January 2024.Details included in the study were maternal high-risk factors, route of delivery, foetal and neonatal outcomes. Results: The women were divided into 2 groups according to the type of meconium staining: thin and thick group. Maternal factors like prolonged labour (8%), oligohydramnios (10%) and Anaemia (18%) preeclampsia (48%), IUGR (6%), GDM (10%) were seen. High caesarean section rate (76%) due to foetal distress was observed in thick meconium. Incidence of birth asphyxia was also higher in thick meconium. 14 had birth asphyxia and 18 had meconium aspiration syndrome. Out of 78 cases of women with thin meconium 76 were with reactive CTG and 2 were with non-reactive CTG who were delivered by caesarean section. Out of 22 cases of women with thick meconium 4 were with reactive CTG and 18 were with non-reactive CTG who were delivered by caesarean section. Out of 100 cases of meconium-stained liquor, no cases of thin had neonatal death and 2 cases of thick had still birth. Conclusions: Meconium-stained liquor markedly enhanced the neonatal morbidity and mortality.